A Space to Speak: Therapeutic Theater to Address Gender-Based Violence. (November 2020) - Arias, Gabrielle; Dennis, Christina; Loo, Stephenie; Lazier, Amy Larson; Moye, Kathleen D.; Moye, Kathleen; O'Connor, Chelsey; Rich, Anna; Weinberg, Molly; Butler, Jason D.
This article examines the experience of eight graduate students in the drama therapy program at Lesley University when creating and performing a theater piece centered around gender-based violence. The performance piece, A Space to Speak, used the performers' real-life stories to highlight their vastly different, yet strikingly similar, experiences and invited the audience to examine their own relationship to those stories. A description of the process used to create and perform the piece is followed by a discussion of the impact the process had on the performers and audience members.